2004
DOI: 10.1007/s00259-004-1484-2
|View full text |Cite
|
Sign up to set email alerts
|

Cell tracking with gadophrin-2: a bifunctional contrast agent for MR imaging, optical imaging, and fluorescence microscopy

Abstract: Purpose: To assess the feasibility of Gadophrin-2 to trace intravenously injected human hematopoietic cells in athymic mice using magnetic resonance (MR) imaging, optical imaging (OI) and fluorescence microscopy. Materials and Methods: Mononuclear peripheral blood cells from GCSF-primed patients were labeled with Gadophrin-2 (Schering AG, Berlin, Germany), a paramagnetic and fluorescent metalloporphyrin, using established transfection techniques with cationic liposomes. The labeled cells were evaluated in vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
63
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(69 citation statements)
references
References 25 publications
5
63
0
1
Order By: Relevance
“…In addition to be tailored to specific properties of already transfected NK cells, our technique provides potential advantages compared to previously described techniques for labeling of other cell types with radioactive, fluorescent or (super-) paramagnetic markers (14)(15)(16)(17)(18)(19)(20). Our MR labeling technique is noninvasive, easy to apply, less toxic (no radiotoxic cell damage) and provides 3D imaging data with high anatomical resolution.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to be tailored to specific properties of already transfected NK cells, our technique provides potential advantages compared to previously described techniques for labeling of other cell types with radioactive, fluorescent or (super-) paramagnetic markers (14)(15)(16)(17)(18)(19)(20). Our MR labeling technique is noninvasive, easy to apply, less toxic (no radiotoxic cell damage) and provides 3D imaging data with high anatomical resolution.…”
Section: Discussionmentioning
confidence: 99%
“…Currently available cell labeling techniques are based on radioactive, fluorescent or (super-)paramagnetic markers (14)(15)(16)(17)(18)(19)(20)(21). Labeling techniques with radioactive markers provide a high sensitivity but limited spatial resolution and the risk of radiotoxic cell damage (14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the percentages of stem cells reaching the carotid artery (Fig. 3B) We and others have shown that intravenous infusion of stem cells does not yield a large number of cells reaching the organ of interest primarily due to the majority of stem cells being trapped inside the lungs [9][10][11]. In an effort to increase the number of stem cells crossing over to the arterial circulation, we analyzed several experimental groups focusing on cell size and adhesion molecules as potential variables.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Consequently, intravenous infusion has been used as the route of cell delivery for a large number of preclinical studies [4][5][6] and is the route of delivery for some early clinical trials [7,8]. However, questions have been raised regarding the ability to obtain a critical number of cells to the area of injury with a systemic intravenous approach [9][10][11]. Previous studies from our laboratory using intravenous administration of mesenchymal stromal cells (MSCs) for regenerative therapy of rat brain injuries demonstrate that few MSCs reach the area of injury, and the vast majority of administered cells are trapped inside the lungs.…”
Section: Introductionmentioning
confidence: 99%